Haementeria lutzi Pinto (Hirudinea: Glossiphoniidae) as a Putative Vector of Trypanosoma evansi (Kinetoplastida: Trypanosomatidae) in the Pantanal Matogrossense - João Carlos Araujo Carreira; Bianca dos Santos Carvalho; Reginaldo Peçanha Brazil; Alba Valéria Machado da Silva (Current Practice in Medical Science Vol. 11, 2022)
The aim of this study was to demonstrate under experimental conditions that Trypanosoma evansi can be mechanically transmitted to Rattus norvegicus by leeches of the species Haementeria lutzi). We also discuss some aspects of Trypanosoma evansi behaviour in leeches following an infectious blood meal, including: a) the parasites quickly moved to the coelomic cavity 10 minutes after ingestion. b) After roughly 10 to 30 minutes in the intestine, trypomastigotes with stumpy and slender shapes and rounded shapes displayed a random dispersion. c) Trypanosomes also infiltrated the salivary glands and proboscis cells 24 hours later. Our findings imply that Haementeria lutzi may play a role as a potential substitute vector for Trypanosoma evansi in Brazilian wetlands.